Hyperinsulinemia does not cause de novo capillary recruitment in rat skeletal muscle. (12th October 2019) - Akerstrom, Thorbjorn; Goldman, Daniel; Nilsson, Franciska; Milkovich, Stephanie L.; Fraser, Graham M.; Brand, Christian Lehn; Hellsten, Ylva; Ellis, Christopher G.
Abstract: Objective: The effect of insulin on blood flow distribution within muscle microvasculature has been suggested to be important for glucose metabolism. However, the "capillary recruitment" hypothesis is still controversial and relies on studies using indirect contrast‐enhanced ultrasound (CEU) methods. Methods: We studied how hyperinsulinemia effects capillary blood flow in rat extensor digitorum longus (EDL) muscle during euglycemic hyperinsulinemic clamp using intravital video microscopy (IVVM). Additionally, we modeled blood flow and microbubble distribution within the vascular tree under conditions observed during euglycemic hyperinsulinemic clamp experiments. Results: Euglycemic hyperinsulinemia caused an increase in erythrocyte (80 ± 25%, P  < .01) and plasma (53 ± 12%, P  < .01) flow in rat EDL microvasculature. We found no evidence of de novo capillary recruitment within, or among, capillary networks supplied by different terminal arterioles; however, erythrocyte flow became slightly more homogenous. Our computational model predicts that a decrease in asymmetry at arteriolar bifurcations causes redistribution of microbubble flow among capillaries already perfused with erythrocytes and plasma, resulting in 25% more microbubbles flowing through capillaries. Conclusions: Our model suggests increase in CEU signal during hyperinsulinemia reflects a redistribution of arteriolar flow and not de novo capillary recruitment. IVVM experiments support this prediction showing increases in erythrocyte and plasma flow and not capillary recruitment.